The business solution to poverty : designing products and services for three billion new customers - Polak, Paul.; Warwick, Mal. (San Francisco : Berrett-Koehler Publishers, Inc., 2013)
The 2.7 billion people living on $2 a day (or less) are not just the world's greatest challenge, they represent an extraordinary market opportunity. By learning how to serve them ethically and effectively, businesses can earn handsome profits while helping to solve one of the world's most intractable problems. The authors show how Zero-Based Design can enable unapologetic capitalists to supply the very poor with clean drinking water, electricity, irrigation, housing, education, healthcare, and other necessities at a fraction of the usual cost and at profit margins attractive to investors.
Preface -- Introduction: eight keys to ending poverty -- Only business can end poverty -- "The poor are very different from you and me" -- What is poverty? -- What can government and philanthropy do? -- Why business is best equipped to fight global poverty -- Zero-based design and the bottom billions -- What to do before you launch your business -- The ruthless pursuit of affordability -- Zero-based design in practice : low-cost drip irrigation -- Design for the market -- Zero-based design in practice : a cautionary tale -- Design for scale -- Zero-based design in practice: safe drinking water for small villages -- Design for delivery the last 500 feet -- Building a mission-driven global business -- Opportunities abound -- It's your turn now -- Resources : takeaways and what we say to critics -- Notes -- Acknowledgments -- About the authors -- Index.
Includes bibliographical references (pages 207-220) and index.
Keywords: Poverty; Social responsibility of business; Industrial management -- Social aspects; Industrial management -- Social aspects; Poverty; Social responsibility of business